Gröna yxor och vita spån: Yx- och mikrospåntillverkning vid Ändebol i sydvästra Södermanland under mellanmesolitikum - Gustafsson, Patrik; Nordin, Mikael (In Situ Archaeologica, 2011)
Excavations of two Mesolithic sites, situated in the south-western part of the county of Södermanland, were completed in the year 2007. The settlements have been dated to around 6300 B.C. At that time the two sites were located in the inner part of a vast archipelago. Among many things, remains from the production of greenstone axes and micro-blades of quartz, as well as flint, were found.